Management of exchange rate regimes in emerging Asia - Ramkishen S. Rajan (Asian Development Bank Institute (ADBI), 2011)
This paper revisits the issue of exchange rate regimes in emerging Asia. It is divided into two main parts. The first part compares de jure and de facto exchange rate regimes in Asia over the decade 1999-2009. It finds that while Asia is home to a wide array of exchange rate regimes, there are signs of gradual movement towards somewhat greater exchange rate flexibility in many of the regional countries. However, the propensity for foreign exchange intervention and exchange rate management among regional central banks remains fairly high in many instances. Beyond a general reluctance of many Asian economies to allow for a benign neglect of their currencies both in terms of managing volatility as well as in terms of leaning against the wind, the sustained stockpiling of reserves in developing and emerging Asian economies since 2000 (interrupted only briefly by the global financial crisis) suggests that they are more sensitive to exchange rate appreciations than to depreciations. This is the focus of the second part of the paper. We find there to be evidence of an apparent fear of appreciation which is manifested in asymmetric exchange rate intervention - i.e., a willingness to allow depreciations but reluctance to allow appreciations. This policy of effective exchange rate undervaluation is rather unorthodox from a neoclassical sense, but is consistent with a development policy centered on suppressing the price of non-tradable goods relative to tradables (i.e., real exchange rate undervaluation). The paper concludes with a few observations on the management of Asian currencies in light of the global financial crisis and concerns about global imbalances.
Keywords: F14; F31; F41; 330; Wechselkurssystem; Finanzmarktkrise; Wechselkurspolitik; Schwellenländer; Asien